Recent Chronology of COVID-19 Pandemic - Siddiqui, Sazada; Alhamdi, Heba Waheeb Saeed; Alghamdi, Huda Ahmed (Frontiers in Public Health, 2022)
COVID-19 is highly contagious and is caused by severe acute respiratory syndrome coronavirus 2. It spreads by means of respiratory droplets and close contact with infected persons. With the progression of disease, numerous complications develop, particularly among persons with chronic illnesses. Pathological investigations indicate that it affects multiple organs and can induce acute respiratory distress syndrome. Prevention is vital and self-isolation is the best means of containing this virus. Good community health practices like maintaining sufficient distance from other people, wearing protective face masks and regular hand washing should be adopted. Convalescent plasma transfusion and the administration of the antiviral Remdesivir have been found to be effective. Vaccines offer lifesaving protecting against COVID-19 which has killed millions and our best bet for staying safe. Screening, suppression/containment as well as mitigation are the strategies implemented for controlling COVID-19 pandemic. Vaccination is essential to end the COVID-19 pandemic and everyone should have an access to them. The current COVID-19 pandemic brought the global economy to a standstill and has exacted an enormous human and financial toll.